2022
DOI: 10.1017/s003329172200143x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of relational-based therapies for the treatment of auditory hallucinations in patients with psychotic disorders

Abstract: Background Auditory hallucinations in patients with psychotic disorders may be very distressing. Unfortunately, a large proportion of individuals are resistant to pharmacological interventions and the gold-standard cognitive-behavioral therapy for psychosis offers at best modest effects. To improve therapeutic outcomes, several therapies have been created to establish a relationship between voice-hearers and their voices. With increasing literature, we conducted a systematic review of dialogical therapies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 54 publications
(93 reference statements)
0
12
0
Order By: Relevance
“…Alongside the development of therapies to target a range of trauma effects in psychosis, there has also been an increased focus on therapies targeting specific difficulties, particularly voice‐hearing. The recognition of associations between trauma and hearing voices (Bailey et al, 2018; Steel, 2015) has led to growing advocacy for the role of psychological treatments for voice‐hearers, including those which emphasise changing the relational dynamics between hearer and voice(s) (Dellazizzo et al, 2021). In this respect, therapies which target traumatic sequelae acting as mechanisms in voice‐hearing have the potential to improve outcomes.…”
Section: Targeted Interventions For Trauma‐related Voices: Talking Wi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside the development of therapies to target a range of trauma effects in psychosis, there has also been an increased focus on therapies targeting specific difficulties, particularly voice‐hearing. The recognition of associations between trauma and hearing voices (Bailey et al, 2018; Steel, 2015) has led to growing advocacy for the role of psychological treatments for voice‐hearers, including those which emphasise changing the relational dynamics between hearer and voice(s) (Dellazizzo et al, 2021). In this respect, therapies which target traumatic sequelae acting as mechanisms in voice‐hearing have the potential to improve outcomes.…”
Section: Targeted Interventions For Trauma‐related Voices: Talking Wi...mentioning
confidence: 99%
“…However, work to date indicates it is possible for some service users to conceptualise, engage with and ameliorate hostile voices using a combination of formulation and dialogue within a context of trauma‐informed working. Combined with evidence from other relational therapies (Dellazizzo et al, 2021), it appears interpersonal dynamics are an important aspect of the voice‐hearing experience and, beyond explicit verbal engagement, should still be considered as a possible treatment strategy when supporting distressed voice‐hearers with a significant history of trauma.…”
Section: Targeted Interventions For Trauma‐related Voices: Talking Wi...mentioning
confidence: 99%
“…Unlike problems such as social anxiety disorder, where social representations may be distorted but remained tethered to genuine individuals and their actions, in psychosis, the representations of social agents may be internally generated, seemingly sui generis in some cases or after becoming untethered from the genuine social agents with whom they are initially identified and instead begin to be perceived as being autonomous social actors [34]. These experiences are a significant driver of distress [101-102] and now a target for therapeutic intervention [103]. The degree to which humans normally attribute agency in otherwise non-agentive contexts is a matter of continuing investigation (see Box 3).…”
Section: Future Directions For Formal Theories Of Social Representati...mentioning
confidence: 99%
“…Following an initial pilot trial (13), a fully powered randomised trial of AVATAR therapy has demonstrated large treatment effects (d = 0.8), against an active control, in reducing the severity of auditory hallucinations in participants identi ed as treatment-resistant (14). A recent systematic review (15) has presented encouraging evidence of effectiveness of AVATAR therapy by researchers working independently of the creators but following the original protocol.…”
Section: Introductionmentioning
confidence: 99%